Challenges implementing a carer support intervention within a national stroke organisation: findings from the process evaluation of the OSCARSS trial. Issue 1 (12th January 2021) - Darley, Sarah; Knowles, Sarah; Woodward-Nutt, Kate; Mitchell, Claire; Grande, Gunn; Ewing, Gail; Rhodes, Sarah; Bowen, Audrey; Patchwood, Emma
Abstract : Objectives: To examine the implementation of an intervention to support informal caregivers and to help understand findings from the Organising Support for Carers of Stroke Survivors (OSCARSS) cluster randomised controlled trial (cRCT). Design: Longitudinal process evaluation using mixed methods. Normalisation process theory informed data collection and provided a sensitising framework for analysis. Setting: Specialist stroke support services delivered primarily in the homes of informal carers of stroke survivors. Participants: OSCARSS cRCT participants including carers, staff, managers and senior leaders. Intervention: The Carer Support Needs Assessment Tool for Stroke (CSNAT-Stroke) intervention is a staff-facilitated, carer-led approach to help identify, prioritise and address support needs. Results: We conducted qualitative interviews with: OSCARSS cRCT carer participants (11 intervention, 10 control), staff (12 intervention, 8 control) and managers and senior leaders (11); and obtained 140 responses to an online staff survey over three separate time points. Both individual (carer/staff) and organisational factors impacted implementation of the CSNAT-Stroke intervention and how it was received by carers. We identified four themes: staff understanding, carer participation, implementation, and learning and support. Staff valued the idea of a structured approach to supporting carers, but key elements of the intervention were not routinely delivered. Carers did not necessarily identify as 'carers', which made it difficult for staff to engage them in the intervention. Despite organisational enthusiasm for OSCARSS, staff in the intervention arm perceived support and training for implementation of CSNAT-Stroke as delivered primarily by the research team, with few opportunities for shared learning across the organisation. Conclusions: We identified challenges across carer, staff and organisation levels that help explain the OSCARSS cRCT outcome. Ensuring training is translated into practice and ongoing organisational support would be required for full implementation of this type of intervention, with emphasis on the carer-led aspects, including supporting carer self-identification. Trial registration number: ISRCTN58414120 .